2017
DOI: 10.1111/jcpt.12509
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of furosemide and mannitol for prevention of cisplatin-induced nephrotoxicity

Abstract: Repetitive administration of low-dose cisplatin concurrent with whole pelvic radiation is associated with magnesium wasting. However, choice of diuretic with pretreatment hydration had no significant impact on the severity of this adverse effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Fourteen factors (sex, age, body surface area [BSA], eGFR, cisplatin dosing/BSA, serum creatinine, aspartate aminotransferase, alanine aminotransferase, total bilirubin, serum albumin, and number of patients concomitantly using magnesium sulfate and with chronic heart disease, hypertension, and diabetes mellitus) were selected as factors associated CIN and/or kidney injury or were deemed a priori to be important demographic characteristics for use in a logistic regression model, which was used to calculate propensity scores. 41 , 42 , 43 A 1:1 PSM analysis was performed using the nearest neighbor matching method with a caliper of 0.20 to reduce the potential bias of patient characteristics. 44 Matching was performed without a replacement treatment, and cases not meeting the matching criteria were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen factors (sex, age, body surface area [BSA], eGFR, cisplatin dosing/BSA, serum creatinine, aspartate aminotransferase, alanine aminotransferase, total bilirubin, serum albumin, and number of patients concomitantly using magnesium sulfate and with chronic heart disease, hypertension, and diabetes mellitus) were selected as factors associated CIN and/or kidney injury or were deemed a priori to be important demographic characteristics for use in a logistic regression model, which was used to calculate propensity scores. 41 , 42 , 43 A 1:1 PSM analysis was performed using the nearest neighbor matching method with a caliper of 0.20 to reduce the potential bias of patient characteristics. 44 Matching was performed without a replacement treatment, and cases not meeting the matching criteria were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…A total of seven studies ( 35 , 52 , 55 , 56 , 58 ) were evaluated in creatinine clearance analysis, divided into saline and furosemide subgroups, depending on the control method. Leu 2021 was the main reason for the heterogeneity in the saline group.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our study, no significant protective effect was observed for furosemide-saline hydration in male rats, but the serum levels of BUN and Cr increased significantly when compared with the CP group in female rats. e protective effect of furosemide like mannitol is still debatable [16], while the neutral effect and adverse effect of furosemide on the kidney also are reported [35][36][37].…”
Section: Discussionmentioning
confidence: 99%